The effects of land drainage on groundwater resources in karstic areas of Ireland - COXON, CATHERINE ELIZABETH (Geological Publishing House, Beijing, China, 1988)
The impact of land drainage on groundwater resources is particularly acute in karst areas because of the unique characteristics of karstic aquifers. Arterial drainage of karst lowlands in Ireland, involving the construction of artificial river channels, has resulted in losses of recharge, lowering of water tables, drying up of seasonal lakes (turloughs), alteration of underground flow routes, and periodic groundwater contamination.
PUBLISHED
Keywords: karst; groundwater; land drainage